2008
DOI: 10.1111/j.1524-4733.2008.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utility Scores for Cancer-Related Anemia through Societal and Patient Valuations

Abstract: The health state utility scores from both groups show a decrement in line with worsening anemia. Furthermore, patients who have experienced cancer-related fatigue rate the more severe levels of anemia much lower than the general public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The utility values representing patients' health-related quality of life (HRQoL) were obtained from published literature [14,[23][24][25]. We primarily used comprehensive data from Nafees et al [23], a study that is widely used in health economic evaluations of lung cancer therapies and which provided a community-based utility model for metastatic NSCLC patients in the UK, using the standard gamble interview and taking different treatment-related toxicities and disease states into account.…”
Section: Health Utility Inputsmentioning
confidence: 99%
“…The utility values representing patients' health-related quality of life (HRQoL) were obtained from published literature [14,[23][24][25]. We primarily used comprehensive data from Nafees et al [23], a study that is widely used in health economic evaluations of lung cancer therapies and which provided a community-based utility model for metastatic NSCLC patients in the UK, using the standard gamble interview and taking different treatment-related toxicities and disease states into account.…”
Section: Health Utility Inputsmentioning
confidence: 99%
“…Recent work on the measurement of health utility for anemiarelated health states has been limited to patients with anemia associated with cancer treatment [5], treatment for hepatitis C [6,7] or renal failure [8]. The Center for the Evaluation of Value and Risk in Health, at Tufts University's Cost-Effectiveness Analysis Registry has included utility weights for different Hgb levels from eight studies [6 -13].…”
Section: Introductionmentioning
confidence: 99%
“…In line with guidelines, physicians tend to refer patients in more severe disease state and with a clear motivation for surgery which may explain the difference between the EQ-5D scores and SG values obtained in this population. In addition, others studies have also reported that patient experiencing the diseases tend to have lower ratings of their health state compared with general population [47].…”
Section: Validitymentioning
confidence: 97%